Sistem SKRINJA: odpiranje podatkov za javnost in napovedna analitika z uporabo umetne inteligence - Kolenko, Paula Jožefa; Krebs, Alenka (OTS 2026 Sodobne informacijske tehnologije in storitve: Zbornik 29. konference, 2026)
In this paper, we present an upgrade of the SKRINJA business intelligence system, a horizontal platform for decision-making support in state administration bodies. In its target state, the system enables the capture, integration and analysis of data from various information sources and provides up-to-date information on key business indicators to support operational and strategic decision-making. In the latest development period, it was upgraded with two new modules: Open Skrinja and Predictive Analytics. The Open Skrinja module enables automated publication of open data and its interactive presentation with business intelligence tools. As the first example of use, data on awarded public contracts was published on the e-JN portal, where they are available to users in the form of interactive Power BI dashboards. The Predictive Analytics module uses machine learning methods to predict future trends. Its usability was tested on data from the Common Agricultural Policy of the Ministry of Agriculture. It enables the prediction of trends in the abandonment of agricultural activity and the preparation of analytical bases for timely planning of measures. The presented solutions were developed as generic services of the SKRINJA platform, so they can also be used in other areas of state administration.